Analysis of Legal Structural Protection of Terrorism Crimes in Indonesia Based on Legal System Theory - Yanto, Yanto (Journal of Legal and Cultural Analytics, 2024)
The enforcement of terrorism cases in Indonesia still has several problems, including the inability to implement Government Regulation Number 77 of 2019 concerning the Prevention of Criminal Acts of Terrorism, and Protection of Investigators, Public Prosecutors, Judges, and Correctional Officers, and the centralized handling of Terrorism cases in Jakarta. In all entities, the enforcement of criminal acts of terrorism is part of the legal structure according to Lawrence M Friedmen's theory which is often used as legal system theory. In this research, the method used is normative juridical research, besides that the research is carried out with a statutory approach, and a case approach. The results showed that Government Regulation Number 77 of 2019 concerning the Prevention of Criminal Acts of Terrorism and the Protection of Investigators, Public Prosecutors, Judges, and Correctional Officers, is still difficult to implement. This is because the guidelines in protecting investigators, public prosecutors, judges, and correctional officers and their families in the case of criminal acts of terrorism who must be given protection by the state from possible threats that endanger themselves, their lives, and/or their property both before, during, and after the case examination process, have not been institutionalized in a regulation or policy by the government to the fullest, based on research, this takes time, not only synergy between stakeholders, such as the budget policy of the finance ministry to the ministry of home affairs and other institutions to sit together to overcome the problems of government regulation number 77 of 2019. On the other hand, the centralized handling of terrorism cases in Jakarta is a priority consideration for the government so that the security factor of the central government in the capital is maximized.